Influence Accounting Internal Control, Utilization Technology Information, Financial Supervision, and Human resources Quality on Reliability local Goverment Finance Reporting (Study in OPD Tangerang City 2016 – 2019) - Rina, Rien Sapta; Andi; Mukhtar (Management Science Research Journal, 2023)
This study aims to examine the effect of internal accounting controls, utilization of information technology, financial supervision, and the quality of human resources on the reliability of local financial reporting in the Local Government Organizations of the City of Tangerang. The technique of determining the sample using purposive sampling technique, sampling is done by taking samples from the population based on certain criteria. The sample criteria taken in this study were employees who carried out financial administration in 15 local government organizations with a total of 71 employees. The type of data used is primary data. Data collection method is done by questionnaire. The analysis model in this study is multiple regression analysis using IBM SPSS Version 25 for windows software. The results of the study show that accounting internal controls, information technology utilization, financial supervision and the quality of human resources have a positive effect on the reliability of local financial reporting in Tangerang City Local Government Organizations.